Analysis of Sharia Banking Products and Services Based on Sharia Principles in Supporting the Modern Islamic Financial System - Muhammad Albahi; Dinda Selvia; Raja Sakti Putra Harahap (LifeSciFi, 2026)
The development of the Islamic economy in Indonesia has encouraged the increasing role of Islamic banking in providing financial services in accordance with Islamic principles and the needs of modern society. This study aims to analyze the implementation of Islamic banking products, financing systems, and digital service innovations in supporting a modern Islamic financial system. The study employed a library research method with a descriptive-analytical approach through data collection from scientific journals, academic books, regulations, and various literature related to Islamic banking. The results show that Islamic banking has three main product groups: fundraising, financing, and service delivery, which are carried out through various contracts such as mudharabah, murabahah, musyarakah, ijarah, and wakalah. Furthermore, the digitalization of services through mobile banking, internet banking, and digital payments has been proven to improve operational efficiency, service accessibility, and public financial inclusion. This study also found that strengthening digital innovation based on Islamic principles is a crucial strategy in increasing the competitiveness of the Islamic banking industry. The implications of this research emphasize the importance of technology integration and Islamic compliance in the development of modern financial services. However, this research is limited to a conceptual approach without direct empirical testing in the field.